Analysis and design of hybrid systems 2006 a proceedings volume from the 2nd IFAC Conference, 7-9 June, 2006, Alghero, Italy - Cassandras, Christos G.
This volume contains the proceedings of ADHS06: the 2nd IFAC Conference on Analysis and Design of Hybrid Systems, organized in Alghero (Italy) on June 7-9, 2006. ADHS is a series of triennial meetings that aims to bring together researchers and practitioners with a background in control and computer science to provide a survey of the advances in the field of hybrid systems, and of their ability to take up the challenge of analysis, design and verification of efficient and reliable control systems. ADHS'06 is the second Conference of this series after ADHS'03 in Saint Malo. * 65 papers selected through careful reviewing process * Plenary lectures presented by three distinguished speakers * Featuring interesting new research topics.